Periods of intense human impact in Central Poland recorded in aeolian, slope, fluvial and organic deposits: https://doi.org/10.26485/AGL/2018/107/7 - Twardy, Juliusz; Forysiak, Jacek; Kittel, Piotr (Acta Geographica Lodziensia, 2018)
The paper summarises and discusses a set of 120 radiocarbon dates of Holocene aeolian, slope, fluvial and peatbog sediments from Central Poland that were deposited under human impact. Based on both the Holocene chronostratigraphic division and archaeological chronology, events that led to the formation of these sediments are presented. A link is made connecting events in aeolian, slope, fluvial and peatbog geosystems to the activity of prehistoric cultures and to settlement development in modern times in Central Poland. Special attention is paid to periods in which the responses of different systems were synchronous to each other.